The Influence of Product Quality, Price and Digital Marketing on Purchase Intention Batik Products in Sungai Penuh City - Fatma Ariani; Enny Sestriyenti; Engla Desnim Silvia; Rina Susanti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2023)
The small industry is currently one of the crucial sectors in advancing the national economy, especially the Kerinci batik business. This study was conducted to discover the influence of the independent variables, namely product quality, price and digital marketing on interest in buying Batik Products. This study's population were Kerinci batik consumers located in Sungai Penuh City. Accidental sampling criteria determine the sample by distributing questionnaires to 50 consumers of Batik Kerinci, especially those in the Sungai Penuh City area. Data analysis consisted of descriptive, classical assumption, and multiple regression tests. Hypothesis testing consists of F test and t test. The study results show that only the product quality and price variables significantly and positively affect purchase intention. In contrast, the digital marketing variables have an effect. However, they are not significant; simultaneously, the product quality, price and digital marketing variables positively and significantly affect purchase intention.